Enhanced TB surveillance efforts in British Columbia First Nation children : a framework for evaluation - Buchholz, Shawna (2009)
Evaluation of programs and implications for public health for First Nations on-reserve children since discontinuation of Bacille-Calmette-Guerine (BCG) vaccine in 2003. In 2003, British Columbia (BC) opted to discontinue routine Bacille Calmette-Guerin (BCG) vaccination for First Nation children and replace this with enhanced tuberculosis (TB) control activities as recommended by First Nations and Inuit Health, Health Canada (Public Health Agency of Canada, National Advisory Committee Statement on BCG, 2004). BCG is the most widely administered vaccine in the world and is used to prevent serious forms of TB in children, most notably TB meningitis and miliary TB (Fine, P., Carneiro, T, Milstien, J. & Clements, C.J., 1999). Evaluation of reports detailing serious adverse events caused by the BCG vaccine in some First Nation children raised concerns that the routine neonatal BCG immunization program may well be associated with unforeseeable and unacceptable health risks (Public Health Agency of Canada, 2004a). The decision to shift from mass vaccination of infants to selective vaccination of high risk groups is guided by criteria established by the International Union against Tuberculosis and Lung Disease (lUATLD) (World Health Organization, 2004). Of significant importance to meeting these criteria, there must be an efficient notification system in place to monitor, case find and treat active TB cases. BC Center for Disease Control (BCCDC) is the centralized health authority for maintaining communicable disease registry and services for the province of British Columbia. All core TB services are delivered by BCCDC in partnership with First Nation & Inuit Health, Pacific Region. To monitor and improve TB control efforts with First Nation reserves, an enhanced surveillance and screening program was developed and implemented in June 2004. Effective evaluation of the enhanced surveillance program will help facilitate future direction for TB control initiatives and priorities with First Nation communities and provide additional research for public health policy.